BRIM‐P: A phase I, open‐label, multicenter, dose‐escalation study of vemurafenib in pediatric patients with surgically incurable, BRAF mutation‐positive melanoma. Issue 5 (19th January 2018) - Chisholm, Julia C.; Suvada, Jozef; Dunkel, Ira J.; Casanova, Michela; Zhang, Weijiang; Ritchie, Natasha; Choi, YounJeong; Park, Jane; Das Thakur, Meghna; Simko, Stephen; Wan Rachel Tam, Nga; Ferrari, Andrea
Abstract: Background: Vemurafenib, a selective inhibitor of BRAF kinase, is approved for the treatment of adult stage IIIc/IV BRAF V600 mutation‐positive melanoma. We conducted a phase I, open‐label, dose‐escalation study in pediatric patients aged 12–17 years with this tumor type (NCT01519323). Procedure: Patients received vemurafenib orally until disease progression. Dose escalation was conducted using a 3 + 3 design. Patients were monitored for dose‐limiting toxicities (DLTs) during the first 28 days of treatment to determine the maximum tolerated dose (MTD). Safety/tolerability, tumor response, and pharmacokinetics were evaluated. Results: Six patients were enrolled (720 mg twice daily [BID], n = 3; 960 mg BID [n = 3]). The study was terminated prematurely due to low enrollment. No DLTs were observed; thus, the MTD could not be determined. All patients experienced at least one adverse event (AE); the most common were diarrhea, headache, photosensitivity, rash, nausea, and fatigue. Three patients experienced serious AEs, one patient developed secondary cutaneous malignancies, and five patients died following disease progression. Mean steady‐state plasma concentrations of vemurafenib following 720 mg and 960 mg BID dosing were similar or higher, respectively, than in adults. There were no objective responses. Median progression‐free survival and overall survival were 4.4 months (95% confidence interval [CI] = 2.7–5.2) and 8.1 months (95% CI = 5.1–12.0), respectively. Conclusions: A recommended and effective dose of vemurafenib for patients aged 12–17 years with metastatic or unresectable melanoma was not identified. Extremely low enrollment in this trial highlights the importance of considering the inclusion of adolescents with adult cancers in adult trials.